2012
DOI: 10.5301/jbm.2012.9348
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hematopoietic cytokines SCF, IL-3, GM-CSF and M-CSF in the diagnosis of pancreatic and ampullary cancer

Abstract: The diagnostic ability of M-CSF and SCF in pancreatic and ampullary cancer should stimulate further studies evaluating their clinical usefulness as tumor markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
4
15
2
Order By: Relevance
“…Our observation is supported by data regarding M-CSF from a previous report by Ławicki et al [33] in breast cancer patients. They are also in line with the observations of other authors studying M-CSF levels in patients with pancreatic cancer [34]. Furthermore, it has observed that M-CSF concentrations are statistically different in every group (the analysis related to CC stage) compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observation is supported by data regarding M-CSF from a previous report by Ławicki et al [33] in breast cancer patients. They are also in line with the observations of other authors studying M-CSF levels in patients with pancreatic cancer [34]. Furthermore, it has observed that M-CSF concentrations are statistically different in every group (the analysis related to CC stage) compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of M-CSF, the specificity reported in the paper by Ławicki et al [37] on cervical cancer was marginally higher than that obtained in our study (92%). M-CSF specificity obtained by Vasiliades [34] et al in the study on pancreatic cancer was lower than ours (62.5%). This discrepancy is probably due to the differences in the types of cancers studied.…”
Section: Discussioncontrasting
confidence: 80%
“…Moreover, IL-6 and its downstream pathways, such as the JAK/STAT pathway, have emerged as important factors in the modulation of cancerassociated inflammation [22]. The serum levels of GM-CSF in pancreatic patients showed a significant positive correlation with the serum levels of carcinoembryonic antigen (CEA), the most widely used pancreatic tumor marker [23]. In this study, we found that the percentages of IL-17A-, IL-6-, GM-CSF-producing cells decreased to varying degrees in splenocytes, mesenteric lymph node cells and tumor cells from embelin treated-mice (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…At this point it should be highlighted, that our cohort comprises 36 ampullary cancers, which is to our knowledge the largest ampullary carcinoma cohort analysed regarding CEA expression in literature thus far. There are many studies regarding CEA serum levels in patients as a tumor marker in different solid cancers 37, 38. In this context Kim et al found in their analyses of 104 ampullary cancers a multivariate significant influence of a CEA serum level > 5 ng/ml and disease recurrence.…”
Section: Discussionmentioning
confidence: 99%